Sustained elevated amounts of circulating procoagulant membrane microparticles and soluble GPV after acute myocardial infarction in diabetes mellitus - Morel, Olivier; Hugel, Bénédicte; Jesel, Laurence; Lanza, François; Douchet, Marie-Pierre; Zupan, Michel; Chauvin, Michel; Cazenave, Jean-Pierre; Freyssinet, Jean-Marie; Toti, Florence (Thrombosis and Haemostasis, 2004)
During myocardial infarction (MI), platelet activation and endothelial apoptosis are responsible for the release of procoagulant membrane-derived microparticles (MP) in the blood flow. MP prothrombotic and proinflammatory properties may be crucial for coronary prognosis. Elevated amounts of circulating procoagulant MP were described in diabetes mellitus (DM), and could be of particular significance in a MI context. We evaluated the prothrombotic status of DM and non-DM (NDM) patients at days 1 and 6 after MI, by measurement of circulating procoagulant MP and soluble GPV (sGPV), the platelet glycoprotein V major fragment released upon thrombin cleavage. Variations were compared to values measured in healthy volunteers (HV). Procoagulant MP were captured onto insolubilized annexin V and quantified by prothrombinase assay. Their cellular origin was assessed. With respect to HV, the levels of procoagulant MP detected at D1 and D6 were elevated in DM and NDM, MP being significantly higher in DM vs. NDM. The high amounts of platelet-derived MP and the correlation between procoagulant MP and sGPV, testify to the central role of thrombin-activated platelets during MI in both DM and NDM subsets. The release of platelet and endothelial cell-derived MP persisted at D6 and was more important in DM, the associated prothrombotic risk being also reflected by higher levels of sGPV. The endothelial damage revealed by endothelial-derived MP was twice that observed in NDM patients. In DM patients presenting cardiovascular events at 6 month follow-up, MP levels were significantly higher at D1 after MI than in those without complication (24.9 ± 4.8 vs. 12.3 ± 2.7 nM PhtdSer, p = 0.02), suggesting a prognostic potential for MP.
Keywords: Apoptosis; thrombosis; atherosclerosis; endothelium damage; platelet stimulation; sCD40 Ligand